FACTORS OF INFLAMMATION IN PATIENTS WITH ARTERIAL HYPERTENSION AND DIABETES MELLITUS - Yarmatov Suvon Tatlibayevich (Journals Park Publishing, 2024)
The aim of the study was to study the relationship between indicators of subclinical inflammation and the degree of organ disorders in patients with isolated arterial hypertension (AH) and in combination with diabetes mellitus (DM). 49 patients were examined, 26 of them with isolated hypertension and 46 with hypertension in combination with diabetes, comparable in gender, age and office blood pressure (BP). The daily monitoring indicators were evaluated blood pressure, left ventricular myocardial hypertrophy, endothelial function. The activity of subclinical inflammation was assessed by blood concentrations of interlekines (IL1a, IL6, IL8, IL10), tumor necrosis factor alpha (TNFa) and C-reactive protein (hsCRP). The presence of insulin resistance and the degree of compensation for diabetes mellitus were assessed. Patients with hypertension in combination with DM have higher rates of SMAD and greater manifestations organ lesions, compared with patients with isolated hypertension. Patients with DM are characterized by greater activity of inflammatory processes. The processes of subclinical inflammation are responsible for both the degree of increase in blood pressure, and for the formation of organ lesions. Indicators of insulin resistance correlate with the concentration of the main markers of inflammation.
Keywords: arterial hypertension; diabetes mellitus; inflammation; metabolic syndrome.